A study on the challenges and possibilities of serving senior citizens in public Libraries of the Colombo Municipal Council, Sri Lanka - Alikhan, Sakeena; Gangabadaarachchi, Varuni (National Institute of Library and Information Sciences, University of Colombo, 2021)
Ageing of population has become a global phenomenon and it could be observed in Sri Lanka too. This growing segment of the older adults' last phase of life is recognized to afford new challenges- declining health and opportunities - more redundant spare time during retirement. A public library is a suitable place available for them to effectively and efficiently spend spare time; however, they face challenges while accessing these services. Therefore, this study investigates the challenges senior citizens confront while accessing services and how libraries can address the issues faced by them. Three public libraries, namely Colombo, Kotehena, Sri Sucharitha in the Colombo Municipal Council limits, were selected based on the proportion of elderly population density. Two qualitative methods - in-depth interviews and focus group discussions, were used to gather information from administrators and users of these three libraries. Thematic analysis was done of the transcribed interviews by using Nvivo software. The result revealed that most senior citizens are happy to spend time in libraries as it is a vibrant place that reduces their loneliness and mental stresses. Nevertheless, they have encountered issues when they use these libraries - locating information in the lending division, dependency due to physical health conditions, lack of awareness of the library services apart from regular. Further, the study found that public libraries have opportunities to manage those challenges through their resources—user education and assistive technology programs, enhance mobile services, resources and infrastructure facilities liaison with relevant authorities and marketing the services to expand seniors' services.
Keywords: Public library service; Older adults; Colombo Municipal Council, Sri Lanka